EVALUATION OF BACITRACIN DISK FOR THE IDENTIFICATION OF GROUP 'A' BETA-HEMOLYTIC STREPTOCOCCI - R.A. Gharagozloo; F. Darougar (Tehran University of Medical Sciences, 1974)
A total of 711 beta-hemolytic streptococci were isolated from throat cultures of patients during 1970-73. These strains were grouped in parallel by the precipitin and bacitracin paper disk method. The former method was established as the standard by which the bacitracin technique was compared. The difference in results was about 5.67%. The greatest error (5.4%) was seen with non-group A strains being sensitive to bacitracin. In spite of this, it was shown to be advantageous to use the bacitracin disk for primary isolation from throat cultures rather than to consider all beta-hemolytic streptococci isolated as group A, which would give a magnitude of error around 16%.